[Legislative bill in the State of Florida proposing the assumption that all illness and disability suffered by fire fighters, paramedics and emergency technicians occurred in the line of duty unless proved otherwise] (Tufts Archival Research Center, 2007)
Legislative bill in the state of Florida requiring all communicable diseases acquired and accidents causing disability will be presumed to have occurred on the line of duty for all fire fighters, paramedics or emergency medical technicians unless proved otherwise. Requires employees of these professions to have thorough physical evaluations prior to employment to rule out the contraction of the disease or disability prior to employment.